Further Comment - Newman, Peter (Review of Economic Studies, 1961)
Journal Article Further Comment Get access Peter Newman Peter Newman Mona, Jamaica Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 28, Issue 2, February 1961, Page 142, https://doi.org/10.2307/2295713 Published: 01 February 1961